Tunable compact narrow band THz sources for frequency domain THz anisotropic spectroscopy - George, D. K. (Proc SPIE Int Soc Opt Eng, 2019)
We demonstrate frequency domain THz anisotropy signature detection for protein crystal models using newly developed compact tunable narrow band THz sources based on Orientation Patterned Gallium Phosphide for turn-key spectroscopic systems.